Pemberdayaan Umat Melalaui Program Distribusi Zakat Produktif Pada Badan Amil Zakat Nasional (BAZNAS) Kabupaten Lumajang - Wibisono, Yusuf (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2019)
This study aims to examine the distribution of zakat carried out by the National Zakat Agency (BAZNAS) in productive zakat assistance programs for the empowerment of people, especially the poor in the Lumajang Regency. This research is a qualitative descriptive study. This research will give a systematic and accurate description of the problems, circumstances and events related to the distribution of productive zakat carried out by the National Zakat Agency (BAZNAS) as it is. Of the several BAZNAS zakat distribution programs that are the focus of the research are productive zakat distribution, both in the provision of revolving productive business capital assistance for individuals and groups. Because zakat can be used for productive efforts in order to help improve the quality of life of the people, especially the poor. Furthermore, from the results of this study, it can be seen that the zakat, infaq and shadaqah (ZIS) distribution program carried out by the BAZNAS in Lumajang Regency proved to be very useful and gave a very positive contribution to the small entrepreneurs in developing their businesses. Revolving capital assistance provided in groups can be better developed, compared to those given individually.